Community structure of macrozoobenthos in seagrass bed on Barrang Lompo Island - Mesalina Tri Hidayani; Ayu Ayu; Nursyahran Nursyahran (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2023)
Macrozoobenthos are bottom animals that play an important role in the productivity of waters in seagrass beds. This study aims to determine the species composition, density of macrozoobenthos, community structure of macrozoobenthos and the relationship between seagrass density and density of macrozoobenthos. The research method used is purposive sampling method, this method is taken based on certain reasons and criteria. This research was conducted in June-July 2022 on Barrang Lompo Island. Sangkarrang District, Makassar City. There were 26 species found consisting of 4 classes namely Bivalvia, Gastropods, Chepalopods and Crustacea with a total of 283 ind and dominated by the Gastropod class, both from the number of species and individual density. Macrozoobenthos community structure on Barrang Lompo Island at station I and II with a moderate diversity index (H'), moderate uniformity index (E') and low dominance index (D). The types of seagrass found at stations I and II were Enhalus acoroides, Thalassia hemprichii, and Cymodocea rotundata. The regression results of the relationship between seagrass density and macrozoobenthos density on Barrang Lompo Island show a weak relationship, which means that seagrass density has no relationship with macrozoobenthos density but macrozoobenthos density is influenced by physical and chemical factors of the waters and the type of sandy substrate.